Experimentally validated numerical model of multi-spectral bands radiative transport in solar receiver/reactor with photo-active porous absorber reacting media. (15th February 2023) - Wu, Lianxuan; Guene Lougou, Bachirou; Jiang, Boshu; Zhang, Hao; Guo, Yanming; Geng, Boxi; Yan, TianTian; Łapka, Piotr; Shuai, Yong
Highlights: The coupling principle of directional multi-spectral bands radiation transfer is given with its numerical calculation and analysis method. Radiation behaviors across high-temperature thermal energy storage media are clarified by equivalent surface and distribution coefficient with a maximum relative error of 3%. The effects of operation conditions, distribution coefficients, and optical properties of covering glasses in solar reactor/receiver are analyzed by advanced experimental validated numerical methods. The control and management strategies of the photothermal field are drawn out by thermal-optical performance analysis of operation processes. Abstract: Solar energy efficient utilization such as solar thermal energy storage and thermochemical conversion technologies is an effective way of closing carbon cycles with systematic green environmental remediation. Understanding the complexity of induced light with its spectrum and intensity feature is crucial for the further optimization of the solar system using a more advanced concept such as photothermal catalysis. This study discussed the radiation transfer processes in detail and clarified the principles and assumptions underlying the photothermal effect in the solar receiver/reactor. In addition, the phenomenon of radiation absorption through the porous interface is discussed and the solution of the equivalent surface is given out. Based on the above discussion, a two-bands numerical model is established with various numerical methods to adapt the properties of different surfaces and irradiation sources. The numerical model is validated by experimental data and used to estimate both spectra and intensity transfer characteristics through the solar reactor. The analysis of optimal operation condition, distribution coefficient, spectral feature of glasses, and thermal-optical performance are presented based on advanced numerical model. This study deepens the understanding of radiative transfer mechanisms in solar energy conversion systems and provides pioneering theoretical guidance with an advanced numerical method for the further optimization of a system-level photothermal catalysis process.